PENGARUH PROFITABILITAS, LIKUIDITAS, DAN STRUKTUR MODAL TERHADAP NILAI PERUSAAHAAN RITEL YANG TERDAFTAR DI BURSA EFEK INDONESIA DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI PEMODERASI - Nupus, Iis Tazkiati; Widayati, Neneng; Fauzi, Fauzi (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This study aims to assess the extent to which profitability, liquidity, and capital structure influence the value of retail companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023, with good corporate governance (GCG) acting as a moderator. The method used in this study is a quantitative approach with panel data regression analysis using Eviews13. The sample consisted of 23 retail companies selected through a purposive sampling method. The study findings indicate that profitability and liquidity do not significantly influence firm value, while capital structure does. Furthermore, GCG is not proven to moderate the effect of profitability and liquidity on firm value, but it can moderate the effect of capital structure on firm value. This study provides important implications for management regarding corporate governance and investment decision-making by investors.